Deity with his consort probably Uma Maheshwar - Temples of India Project Team (Jio Institute, 2024)
The interiors of the Kumbheshwar Mahadev Temple are austere, barring a few sculptures. One of the devakoshthas (niches) in the wall of the mandapa (pillared hall) has a deity with his consort probably Uma Maheshwar.